Peran Kuasa Hukum dalam Penyelesaian Sengketa Kepabeanan dan Cukai pada Pengadilan Pajak (Studi Kasus Putusan Nomor 1430/B/PK/Pjk/2026) - Singgih Januratmoko; Moch Abdan Salam; Zainal Arifin Hossein (Yayasan Kawanad, 2026)
This study aims to analyze the role of legal counsel in resolving customs and excise disputes before the Tax Court based on Decision Number 1430/B/PK/Pjk/2026, the application of tax procedural law, and the legal considerations of judges in deciding customs and excise administrative disputes. This study employs normative legal research using a statutory approach and a case approach. The results show that legal counsel plays a role in assisting the parties through the preparation of legal arguments, submission of evidence, and legal defense during court proceedings. The application of tax procedural law in the case is reflected in the examination of the dispute, submission of evidence, and the implementation of judicial review proceedings. The judges’ considerations in deciding the case were based on material truth, the principle of legality, and legal certainty in assessing the dispute over the classification of imported goods and import duty rates. The findings also show that the role of legal counsel in the case was related to the ability to formulate legal arguments and present evidence consistent with the facts and applicable laws and regulations. Therefore, the role of legal counsel in resolving customs and excise disputes is not limited to assisting the parties but also involves the preparation of legal arguments and presentation of evidence during court proceedings.